Assessment of seismic design procedures based on the total cost. - Lagaros, Nikos D.
The assessment of seismic design codes has become the subject of intensive research work which revealed several weak points of the codes that originated from the limitations in predicting with acceptable precision the response of a structure under a moderate or severe earthquake. Most of the seismic design codes belong to the class of prescriptive procedures, where if certain constraints are fulfilled, the structure is considered safe. Prescriptive design procedures fail to provide acceptable levels of structural performance over its life because, in most of them, the structure is assessed using only one design earthquake. Performance-based design is a different philosophy for designing against hazards; the structure is designed to meet a number of performance objectives. The objectives of this study is to compare the initial and limit state-dependent cost of an RC building designed either to meet the provisions of the Greek national seismic design code or based on a performance-based design procedure. Two were the most important findings of this study: (i) the initial cost for an RC structure, designed to permit elastic behaviour for the response spectrum of the Greek national seismic code, is not prohibitive and (ii) that an RC structure based on the proposed performance-based design procedure lead to economical designs with respect to the total cost compared to a code conforming design.
Keywords: Prescriptive design procedures; Performance-based design; Limit state-dependent cost; Pushover analysis